(3GdNUGFU aj GdfMhs - (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEfg bO hbY aj Yde GdfMh eHGMK ZQjHI hahGFO YLjHI JJYdb HGdGSe hGdaYd hGdMQa s
(3BNQgG (B:s
(3aGdbVGA Ydi gPg GdVeGFQ NQhLgG ef GdGSejI dCLd YOe GdEYQGH dG jSJbje gPG BNQ cJGH GdNUGFU aj GdfMh s
(3fSNI ocJHJ Hbde fSNj ajg VHWs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B385 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B117 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs